(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Jumawan JH, Ruales JJJ, Avila MCA. 2022. New distribution record of Varuna litterata from Caraga Region, Philippines: Analysis on morphometry, length/width-weight relationship, and condition factor. Biodiversitas 23: 2935-2942. The study reported the occurrence of Varuna litterata in its habitat as a new record in Caraga Region, Philippines. The crab samples were collected using a hand-picked method and were of marketable sizes. There were 14 morphometric traits measured with the corresponding weight and sex of each specimen. Majority of the crab samples were medium-sized, with weight ranging from 11-20 grams, a carapace width range of 28-34 cm, and a carapace length range of 27-32 cm. Exploratory analysis of length /width-weight data fits the power regression model depicted into graphs. A strong relationship and highly significant was observed on pooled samples of WT-CW variables (R2: 0.9229: P<0.001) and WT-CL variables (R2: 0.9197); P<0.001). The derived log-transformed for WT-CW relationship was logWT: -2.7994+2.6456 logCW. Results suggest that carapace length and width tend to be smaller relative to the weight, which is an indication of a negative allometric growth pattern. The computed Fulton’s condition factor was higher in males than females, as supported by Kruskal Wallis test (P<0.001). The data provides baseline information for comparing similar studies and in understanding the population dynamics of this crab species.